Nonsignificant associations between measures of inhibitory control and walking while thinking in persons with multiple sclerosis - Sandroff, Brian M; Benedict, Ralph H; Motl, Robert W (Archives of physical medicine and rehabilitation, 2015)
To examine whether inhibitory control measures were associated with the dual-task cost (DTC) of walking in persons with multiple sclerosis (MS) and matched controls without MS. Cross-sectional study. University research laboratory. The sample (N=56) included ambulatory persons with relapsing-remitting MS (n=28 [26 women, 2 men]; median Expanded Disability Status Scale score, 3.0) from the local community and controls (n=28) matched by age, sex, body mass index, and education. Not applicable. All participants underwent a modified flanker task followed by 4 trials of the timed 25-foot walk. The first 2 trials involved walking as quickly as possible only (single-task condition), and the second 2 trials involved walking as quickly as possible while naming alternate letters of the alphabet (dual-task condition). Walking speed under single- and dual-task conditions was used to compute a DTC of walking. Persons with MS demonstrated a similar DTC of walking compared with matched controls, but performed more poorly on inhibitory control measures. Interestingly, inhibitory control measures were not associated with DTC of walking in the MS sample (all |ρ|<.26, P>.19), but were associated with DTC of walking in controls (all |ρ|>.42, P<.03). Inhibitory control based on modified flanker performance might not be associated with DTC of walking in persons with MS.